2008
DOI: 10.1186/1752-1947-2-355
|View full text |Cite
|
Sign up to set email alerts
|

Array comparative genomic hybridisation-based identification of two imbalances of chromosome 1p in a 9-year-old girl with a monosomy 1p36 related phenotype and a family history of learning difficulties: a case report

Abstract: Introduction: Monosomy 1p36 is one of the most common terminal deletion syndromes, with an approximate incidence of 1 in every 5000 live births. This syndrome is associated with several pronounced clinical features including characteristic facial features, cardiac abnormalities, seizures and mental retardation, all of which are believed to be due to haploinsufficiency of genes within the 1p36 region. The deletion size varies from approximately 1.5 Mb to 10 Mb with the most common breakpoints located at 1p36.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In fact, molecular cytogenetic analysis performed in 1 patient presenting with MR and learning disability detected the presence of GABRD loci. These data suggested to exclude the involvement of GABRD in the neurological manifestations [36]. Moreover, the 1p36.32 region was found deleted in a small percentage of isolated MR [16], in a number of patients presenting with mild MR and/or behavioral problems and/or learning disability [12,24,25,26,27,28] and in a patient presenting with MR and altered regulation of the circadian rhythm such as sleeping disorders [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, molecular cytogenetic analysis performed in 1 patient presenting with MR and learning disability detected the presence of GABRD loci. These data suggested to exclude the involvement of GABRD in the neurological manifestations [36]. Moreover, the 1p36.32 region was found deleted in a small percentage of isolated MR [16], in a number of patients presenting with mild MR and/or behavioral problems and/or learning disability [12,24,25,26,27,28] and in a patient presenting with MR and altered regulation of the circadian rhythm such as sleeping disorders [26].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the finding of a patient bearing a complex rearrangement including 1p36.32 deletion in which GABRD locus was not involved suggested that the neurological features might be correlated to the anomalous expression of other genes [36]. The patient, a 9-year-old female, presented with dysmorphic features including a small mouth with heaped-up palate, small chin and small overfolded ears, straight eyebrows, fifth finger clinodactyly and short toes.…”
Section: Cytogenetics and Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Apart two previously known candidate genes (SKI and PEX10), we drawn attention to three genes mapped to this region: PRKCZ, PLCH2, and HES5. Recently, Fitzgibbon et al (2008), based on the expression of PLCH2 gene in cerebral cortex, speculated on a possible association between PLCH2 deletion and learning difficulties, developmental delay and speech delay in a patient with complex rearrangement of 1p36.…”
Section: Discussionmentioning
confidence: 99%